2016
DOI: 10.1371/journal.pone.0158176
|View full text |Cite
|
Sign up to set email alerts
|

Small Incision Lenticule Extraction (SMILE) versus Femtosecond Laser-Assisted In Situ Keratomileusis (FS-LASIK) for Myopia: A Systematic Review and Meta-Analysis

Abstract: PurposeThe goal of this study was to compare small incision lenticule extraction (SMILE) with femtosecond laser-assisted in situ keratomileusis (FS-LASIK) for treating myopia.MethodsThe CENTRAL, EMBASE, PubMed databases and a Chinese database (SinoMed) were searched in May of 2016. Twelve studies with 1,076 eyes, which included three randomized controlled trials (RCTs) and nine cohorts, met our inclusion criteria. The overall quality of evidence was evaluated using the Grading of Recommendations Assessment, De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 42 publications
3
63
0
2
Order By: Relevance
“…Symptoms measured with the OSDI are not usually correlated with clinical signs. [7] In spite of the fact that changes in the OSDI and in some clinical signs can be produced after refractive surgery [10] or after treatments,[29] there are not usually correlations between objective measures and subjective questionnaires. Our experiments are consistent with these previous findings, either for VK or OQAS, even though some authors have reported significant non-linear correlations between NIBUT and OSDI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms measured with the OSDI are not usually correlated with clinical signs. [7] In spite of the fact that changes in the OSDI and in some clinical signs can be produced after refractive surgery [10] or after treatments,[29] there are not usually correlations between objective measures and subjective questionnaires. Our experiments are consistent with these previous findings, either for VK or OQAS, even though some authors have reported significant non-linear correlations between NIBUT and OSDI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a less invasive technique named SMILE (small incision lenticule extraction) has been proven to reduce the postoperative incidence of dry eye symptoms in comparison to LASIK, although no clear differences in objective clinical signs have been found between procedures. [10] There are numerous diagnostic tests for dry eye that are not widely accepted yet and are often not reproducible, probably due to the complexity of the disease and the high variability between seasons, time, examiners, etc. [11] New technologies have emerged in order to assess objectively the tear film in a non-invasive way.…”
Section: Introductory Textmentioning
confidence: 99%
“…Admittedly initial studies report SMILE efficacy comparable to standard (wavefront-optimized) LASIK showing essentially "equal" postoperative results. [15][16][17][18][19][20][21][22] Investigators recently reported comparable visual outcomes when comparing wavefront-optimized to topography-guided profiles in a contralateral eye study. 26 However, this study did did not use topography-guided modification (TMR) of the clinical refraction in the respective treatments, something that was the backbone of the refractions used in our study herein and may explain the difference in outcomes.…”
Section: Objective Scatter Index and Low Contrast Sensitivity Measurementioning
confidence: 99%
“…SMILE is comparable to femtosecond laser-assisted in situ keratomileusis (FS-LASIK) in terms of safety, efficacy, and predictability. 5 , 6 Moreover, it has the advantages of better ocular surface stability and biomechanical strength compared to FS-LASIK. 6 10 It provides precise visual acuity and quality and is increasingly being preferred for the treatment of myopia and myopic astigmatism owing to the enhanced patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%